Cytotoxicity study of dimethylisatin and its heterocyclic derivatives - Mohammad Mamun Hossain, Nazrul Islam, Rahat Khan and Md. Rabiul Islam (Bangladesh Pharmacological Society, 2007)
Isatin derivatives are bioactive molecules. To study the cytotoxicity and eventually the anticancer activities against cancer cell lines, a series of dimethyl-substitituted isatin derivatives (4-8) starting from isatin thiosemicarbazones (3) had been synthesized in high yields. Investigation of the cytotoxicity of these compounds was carried out against brine shrimp by lethality bioassay. The present study shows that compounds 4, 5, 6 and 8/ with heterocyclic moiety had pronounced cytotoxicity whereas 7, 7/ and 8 were moderately active. It is remarkable that the substituent, X = -OCH3 has greater activity than the bromine atom in this series.